Oncolytic measles virus encoding interleukin-12 mediates potent antitumor effects through T cell activation - Veinalde, Rūta; Großardt, Christian; Hartmann, Laura; Jäger, Dirk; Kalle, Christof von; Ungerechts, Guy; Engeland, Christine Elisabeth (OncoImmunology, 2017)
Combination of oncolytic virotherapy with immunomodulators is emerging as a promising therapeutic strategy for numerous tumor entities. In this study, we developed measles Schwarz vaccine strain vectors encoding immunomodulators to support different phases in the establishment of antitumor immune responses. Therapeutic efficacy of the novel vectors was evaluated in the immunocompetent MC38cea tumor model. We identified vectors encoding an IL-12 fusion protein (MeVac FmIL-12) and an antibody against PD-L1 (MeVac anti-PD-L1), respectively, as the most effective. Treatment of established tumors with MeVac FmIL-12 achieved 90% complete remissions. Profiling of the tumor immune microenvironment revealed activation of a type 1 T helper cell-directed response, with MeVac FmIL-12 ensuring potent early natural killer and effector T cell activation as well as upregulation of the effector cytokines IFN-γ and TNF-α. CD8+ T cells were found to be essential for the therapeutic efficacy of MeVac FmIL-12. Results of this study present MeVac FmIL-12 as a novel approach for targeted IL-12 delivery and elucidate mechanisms of successful immunovirotherapy.